Tanaidaceans from Brunei, IV. The Families Kalliapseudidae, Pagurapseudopsidae, Parapseudidae and Apseudidae (Crustacea: Peracarida: Tanaidacea: Apseudomorpha), with descriptions of a new genus and six new species - Bamber, R.N. (Zootaxa, 2013)
Apseudomorph tanaidaceans from recent samples of the South China Sea benthos off Brunei have been examined. The habitats were sandy substrata from between 5 and 90 m depth. Fourteen species of the four families considered here were discovered. A new species of Tanapseudes is described. The distribution of Phoxokalliapseudes gobinae is analyzed. Biropalostoma goofi is recorded for the first time in Brunei waters. One new species of the Apseudidae (in the genus Bunakenia) and four new species of the Parapseudidae (one each in the genera Platylicoa and Pakistanapeudes, and two in a new genus Actenos, of the subfamily Pakistanapseudinae) are described. The genus Platylicoa is moved to the Pakistanapseudinae, and the genus Hainanius is returned to the Parapseudidae (Parapseudinae). Apseudes tenuicorporeus is moved from Biropalostoma to the new pakistanapseudin genus described herein.